A POLITICAL ECONOMY ANALYSIS OF THE PAPUA CONFLICT: NATURAL RESOURCE CONTROL, CUSTOMARY LAND RIGHTS, AND THE DYNAMICS OF RESISTANCE MOVEMENTS IN PAPUA - Ahmad Taufan Damanik (Academic Solution Publisher, 2026)
This study examines how conflicts over natural resources and customary land shape political resistance in Papua. Using qualitative document analysis, it reviews academic publications, government documents, statistical reports, church statements, and civil society sources. The findings show that unequal resource control, land dispossession, weak implementation of Free, Prior, and Informed Consent, ecological degradation, and limited Indigenous participation undermine state legitimacy and intensify resistance. However, shared grievances among the OPM, Indigenous communities, churches, and civil society do not necessarily indicate formal organizational consolidation. Sustainable conflict resolution requires recognition of customary rights, meaningful participation, distributive justice, accessible grievance mechanisms, and differentiated dialogue.